Analysis of Translation Techniques in the journal abstract of IJAI 6(1) - Afriani; Pratiwi; Panessai, Ismail Yusuf; Iskandar, Dedy; Effendi, Eddy (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Penerjemahan berperanan penting dalam sebuah komunikasi. Penerjemahan adalah serangkaian tindakan analitis terhadap teks sumber (TSu) untuk dialihbahasakan kedalam teks sasaran (TSa) yang sepadan sehingga menghasilkan terjemahan yang baik dan dapat di mengerti oleh pembaca. Penerjemahan tidak hanya sekedar mengubah kata, tetapi juga mentransfer kesepadanan budaya dengan budaya bahasa TSu dan penerima bahasa tersebut dengan sebaik-baiknya. Salah satu naskah yang selalu menggunakan proses penerjemahan adalah adalah abstrak. Abstrak bertujuan untuk memberikan gambaran umum tentang isi sebuah tulisan karya ilmiah. Karya ilmiah ini merupakan studi kasus penerjemahan abstrak artikel yang diterbitkan di International Journal of Artificial Intelligence (IJAI) pada Terbitan 6(1) tahun 2019. Tujuan penelitian ini adalah untuk mendeskripsikan proses penerjemahan yang dilakukan pada teks sumber (TSu) ke dalam teks sasaran (TSa) untuk menghasilkan terjemahan yang sepadan dan juga metode atau teknik yang muncul dalam penerjemahan teks sumber (TSu) kedalam teks sasaran (TSa). Dari penelitian yang dilakukan dapat disimpulkan bahwa dalam proses penerjemahan yang dilakukan pada teks sumber (TSu) ke dalam teks sasaran (TSa) harus mempertimbangkan faktor-faktor yang terkandung di dalam teks tersebut agar mendapatkan hasil terjemahan yang sepadan dan dapat difahami dengan baik oleh pembaca. Faktor utama yang sangat mendukung adalah bahwa penerjemah harus mengetahui istilah-istilah dalam TSu dan memahami penggunaan istilah tersebut sehingga penerjemah bisa dengan mudah menerjemahkan naskah TSu ke dalam TSa. Selain itu, teknik penerjemahan yang banyak digunakan dalam kedua naskah adalah teknik transposisi, teknik meminjam kata baik murni maupun dengan perubahan serta teknik adaptasi dan calque. Analysis of Translation Techniques in the journal abstract of IJAI 6(1) Abstract: Translation plays an important role in communication. Translation is a series of analytical actions on the source text (TSU) to be translated into equivalent target text (TSA) so as to produce a good translation and can be understood by the reader. Translation does not just change the word, but also transfers the cultural correspondence to the culture of the TSu language and its recipient as best as possible. One of the texts that always uses the translation process is an abstract. Abstract aims to provide an overview of the contents of a scientific paper. This scientific work is a case study of translating article abstracts published in the International Journal of Artificial Intelligence (IJAI) in Issue 6 (1) in 2019. The purpose of this research is to describe the translation process carried out on the source text (TSu) into the target text (TSa) to produce an equivalent translation and also the methods or techniques that appear in the translation of the source text (TSu) into the target text (TSa). From the research conducted, it can be concluded that in the translation process carried out on the source text (TSu) into the target text (TSa) must consider the factors contained in the text in order to get a translation result that is equivalent and can be well understood by readers. The main factor that is very supportive is that the translator must know the terms in TSu and understand the use of these terms so that the translator can easily translate the TSu script into TSa. In addition, the translation techniques that are widely used in the two texts are transposition techniques, techniques for borrowing words both pure and with changes as well as adaptation and calque techniques. Keywords: Abstract, Couplet, Journal, Translation Technique, TSu ≈ TSa.